Rat-Bite Fever: Developing and testing a modified time-kill protocol based on Edberg and Edberg 1983 experiemnt in order to test S. moniliformis growth in 0.05% SPS and proposed growth curve. (28th October 2021) - Szewc, A M; Bell, M; Kelly, A; Humrighouse, B; McQuiston, J
Abstract: Introduction/Objective: Streptobacillus moniliformis is the primary causative agent of rat-bite fever (RBF) and Haverhill fever (HF). Rat-bite fever and Haverhill fever are difficult to diagnose in a clinical setting and are likely severely under-represented and under-reported worldwide. Clinical presentation often includes fever, chills, myalgia, headache, and vomiting. Patients may also develop a maculopapular rash covering their extremities approximately 2-4 days after onset of fever followed by polyarthritis in roughly 50% of patients with a mortality rate of 10-13% if left untreated. This is further complicated by the fact that submission and processing guidelines of clinical samples for the recovery of the organism are based on 'outdated' techniques and clinical laboratory methods that are over 50 years removed from current procedures, instrumentation and guidance. Methods/Case Report: DNA from collected frozen time-point samples, were collected (n=84) and extracted using an in-house custom protocol utilizing 180 µl of bacterial lysis buffer with 20 µl of PCR grade proteinase K, for a total of 200 µl. The blood culture time-point samples were then thawed on ice, and 200 µl of blood culture sample was then added to the lysis mix, vortexed and incubated at 65°C for 10 minutes (an additional 95°C inactivation step was omitted to avoid whole blood clotting). After incubation, each sample was vortexed briefly again and extracted using the Roche automated MagNA Pure Compact instrument with an initial input volume of 400 µl and stored in a final elution buffer volume of 100 µl. All quantatitive time kill data was colleced via a CDC in-house designed PCR assay developed for S. moniliformis. Results (if a Case Study enter NA): Experimenting with varying amounts of blood inoculum, 10 ml of blood was determined to provide the best results for detection and growth/viability as well as propose a theoretical growth curve for the organism. Conclusion: We found that in 100% of the isolates tested (and all the variations of testing within), SPS (up to a concentration of 0.05 % w/v) in commercially available blood culture bottles appeared to be inactivated, allowing for the growth detection and culturing of S. moniliformis using an automated continuous blood culture system when 10 ml of blood was inoculated.